The Citizens in Citizen Science: Demographic, Socioeconomic, and Health Characteristics of Biodiversity Recorders in Ireland. (6th August 2020) - Mac Domhnaill, Ciarán; Lyons, Seán; Nolan, Anne
Citizen science allows members of the public to engage with scientific inquiry, and is increasingly being employed to monitor environmental change. Some previous research explores the demographic characteristics of participants in environmental citizen science projects. Design of recruitment campaigns and selection of activities for citizen science projects could benefit from a better understanding of participants' demographic and socioeconomic characteristics, as well as participants' health, their well-being status, and their level of physical activity. In addition, this type of information can provide a baseline for examining effects of engaging in citizen science on participants' health and well-being in later research. This paper reports results from a survey of a group of environmental citizen scientists engaged in observation and monitoring activities who have recently registered as biodiversity data recorders in Ireland. The survey employs questions drawn from existing large-scale socioeconomic surveys in Ireland, so the characteristics of biodiversity recorders can be compared with those of the wider population. Differences in proportions are tested for statistical significance, and Blinder-Oaxaca decomposition methods are applied to strip out compositional differences when comparing health status and physical activity. Results show that biodiversity recorders are more highly educated, more middle-aged, more rural, better-off, and more active in the labour force than the general population. They are deeply concerned about threats from the decline or extinction of species and ecosystems, they classify environmental protection as very important, and they believe that individuals have a role to play in protecting the environment. Biodiversity recorders are more physically active than the wider population, and mixed results are found for generalised health and mental health status.